Bridging the Under-Five Mortality Gap for Africa in the Era of Sustainable Development Goals: An Ordinary Least Squares (OLS) Analysis - Michael Acheampong; Chukwudi Ejiofor; Abraham Salinas-Miranda; Foday M. Jaward; Michael Eduful; Qiuyan Yu (Ubiquity Press, 2018)
Background: While Africa achieved significant progress in reducing under-five mortality rate (U5MR) in the MDGs era, it did not achieve the set target and still has the highest average of 81 deaths per 1000 live births compared to a global average of 43 deaths. The SDG number 3 has set a new target of reducing U5MR to 25 deaths per 1000 births in the world, which serves a huge challenge, especially for Africa. Socioeconomic inequities that remain unaddressed across countries account for Africa's high U5MR. Unless there is adequate prioritization of important socioeconomic, healthcare, and environmental factors, the new SDGs target will be hindered. Objectives: In this study, our primary objective was to analyse and assess factors that account most for the U5MR inequities between Africa and the rest of the world. Methods: We conducted a series of ordinary least squares (OLS) regression-based prioritization analysis of socioeconomic, healthcare, and environmental variables from 43 African countries in a pool of 109 countries from around the world to understand the most important factors that account most for the high U5MR in Africa. Findings: The results suggest that the most critical category for bridging the U5MR gap with the rest of the world is improved healthcare access. However, with all categories examined together, the OLS regression showed that the most important factors that accounted for Africa's high U5MR compared with the rest of the world were, in order: fertility rate, access to improved water, total health expenditure per capita, access to improved sanitation, and female employment rate. Conclusions: The findings reveal that Africa will significantly benefit from interventions geared towards both the treatment and prevention of acute infectious diseases in the form of providing affordable maternal healthcare services, as well as providing access to improved drinking water and sanitation.